Agronomic characterization and heterosis in watermelon genotypes - Tiago Lima do Nascimento; Flávio de França Souza; Rita de Cássia Souza Dias; Edson Ferreira da Silva (Pesquisa Agropecuária Tropical, 2018)
In order to increase the yield of vegetables of agronomic interest, heterosis has been studied in view of the superiority of hybrids, if compared to genotypes obtained by free pollination. This study aimed to estimate the relative heterosis in watermelon hybrids, regarding the most important agronomic traits, in order to develop future cultivars. The genotypes 'JNY', 'ORA', 'KOD', 'SOL', 'CHG', 'PEA' and all hybrids among them were used, totaling 36 treatments. A randomized block design, with three replications and five-plant plots, was used. The genotypes 'ORA', 'SOL', 'CHG' and 'PEA' were promising for the development of watermelon hybrids with higher weight, whereas 'JNY' and 'KOD' provided combinations with lower fruit weight and smaller seeds, indicating their potential for the development of cultivars of the 'ice box' type. The hybrids 'CHG x ORA' and 'ORA x CHG' were promising to meet the market demand for larger fruits, while 'KOD x JNY' and 'JNY x KOD' could be targeted to the market of smaller fruits.